2000
DOI: 10.1097/00002820-200008000-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of the Comprehensive Coping Strategy Program on Clinical Outcomes in Breast Cancer Autologous Bone Marrow Transplantation

Abstract: Patients with breast cancer who undergo autologous bone marrow/peripheral blood stem cell transplantation (ABMT) cope not only with a life-threatening medical treatment, but also with multiple, interrelated symptoms including pain, fatigue, psychological distress, and nausea. The purpose of this study was to determine, in a randomized controlled clinical trial, whether a comprehensive coping strategy program (CCSP) was effective in significantly reducing pain, fatigue, psychological distress, and nausea in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(74 citation statements)
references
References 30 publications
2
69
0
3
Order By: Relevance
“…In the same line, Mohamed [33] who found that a decrease in fatigue severity in the study group with a highly statistical significance difference between the study group, who followed the nursing management program as progressive muscle relaxation technique, patient education about diet, life style modification than the control group. Página [34] recommended that lifestyle changes, such as exercising more, relieving stress, and eating a healthy, well-balanced diet can help ease fatigue Also, these findings are in agreement with the results of Gaston-Johansson et al [35] who reported that Dood [36] reported similar findings that education of fatigue management and adequate information regarding self-help measures were valuable in helping subjects deal with the side effects o f chemotherapy. Dood's research indicated that information was not enough to influence fatigue in subjects receiving chemotherapy.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In the same line, Mohamed [33] who found that a decrease in fatigue severity in the study group with a highly statistical significance difference between the study group, who followed the nursing management program as progressive muscle relaxation technique, patient education about diet, life style modification than the control group. Página [34] recommended that lifestyle changes, such as exercising more, relieving stress, and eating a healthy, well-balanced diet can help ease fatigue Also, these findings are in agreement with the results of Gaston-Johansson et al [35] who reported that Dood [36] reported similar findings that education of fatigue management and adequate information regarding self-help measures were valuable in helping subjects deal with the side effects o f chemotherapy. Dood's research indicated that information was not enough to influence fatigue in subjects receiving chemotherapy.…”
Section: Discussionsupporting
confidence: 81%
“… The researcher started the data collection and implementation of the program from the November 2013 to December 2013.  The patient assessment sheet was filled by the researcher through personal interview, within [30][31][32][33][34][35][36][37][38][39][40] minutes, the purpose of the study was explained to them and an informed consent to participate in the study was taken.  Intervention program.…”
Section: Data Collection Methodmentioning
confidence: 99%
“…As with exercise interventions, a growing body of empiric data supports the use of psychosocial interventions for the management of CRF. Randomized, controlled clinical trials have examined a variety of psychosocial interventions in cancer survivors during and after treatment (Table 2) [139][140][141][142][143][144][145][146][147][148][149][150][151][152][153].…”
Section: Psychosocial Interventionsmentioning
confidence: 99%
“…Both anxiety and depression may be linked with subsequent fatigue, but these diagnoses may be complicated because some frequent symptoms are due to the underlying fatigue. Interventions to reduce stress and increase psychosocial support include education 17 , support groups 18 , individual counseling 19 , comprehensive coping strategies 20 , stress management training 21 , and individualized behavioral intervention 22 . Other interventions include listening to a guided-imagery tape daily, prioritizing daily activities, and encouraging discussion of how fatigue has affected lifestyle and emotional well-being.…”
Section: Psychosocial Interventionsmentioning
confidence: 99%